2018
DOI: 10.1007/s00330-018-5413-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast-enhanced magnetic resonance angiography: a reliable clinical tool for evaluating transplant renal artery stenosis

Abstract: • Good or excellent image quality was found in 95.4 % of examinations. • Non-contrast-enhanced MRA can clearly map transplant renal artery anatomy. • Non-contrast-enhanced MRA is a reliable tool to detect TRAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Several previous studies demonstrated that 3D bSSFP-based NCE-MRA sequences could evaluate renal transplant arteries. 8,16,[19][20][21] In this study, adequate evaluation of transplant artery stenosis using 3D bSSFP MRA was feasible in 38 out of 43 cases (88%). Previous studies have reported slightly higher numbers, which included 87% in a study of 15 patients, 16 and 95.4% of cas-es in a larger study of 369 examinations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several previous studies demonstrated that 3D bSSFP-based NCE-MRA sequences could evaluate renal transplant arteries. 8,16,[19][20][21] In this study, adequate evaluation of transplant artery stenosis using 3D bSSFP MRA was feasible in 38 out of 43 cases (88%). Previous studies have reported slightly higher numbers, which included 87% in a study of 15 patients, 16 and 95.4% of cas-es in a larger study of 369 examinations.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have reported slightly higher numbers, which included 87% in a study of 15 patients, 16 and 95.4% of cases in a larger study of 369 examinations. 19 The differences in the reported success rate could be related to differences in the study design, technique implementation, or patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes in detecting stenosis by MRA appear to be comparable with DSA and US [110]. Compared to DSA, NCE-MRA displays a sensitivity up to 100%, a specificity ranging from 85.7 to 90% and an accuracy of 91-96.6% [104,105,111,112]. Studies using CE-MRA report a comparable sensitivity and specificity [113][114][115][116][117].…”
Section: Long-term Vascular Complicationsmentioning
confidence: 98%
“…When the donor transplant artery is excessively long, artery kinking can occur, resulting in a turbulent blood flow. Several cases of artery kinking successfully depicted with MRA are described [104,105].…”
Section: Short-term Vascular Complicationsmentioning
confidence: 99%
“…NCE-MRA including bSSFP techniques have shown to be reliable in depicting normal [27] and stenosed renal arteries [31][32][33], as well as of transplanted renal arteries [34]. Similarly, REACT may be a viable alternative to screen for and monitor patients with renal artery stenosis.…”
Section: Assessment Of Renal Artery Patencymentioning
confidence: 99%